FORMULASI EKSTRAK BUAH NAGA MERAH (Hylocereus polyrhizus ) SEBAGAI SEDIAAN PEMERAH PIPI (BLUSH ON) - Herviani Sari; Firdaus Fahdi (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2021)
Dragon fruit contain high antosianin, sources of antosianin can be optained from pink colored fruit and vegetables to red. The natural properties of antosianin can be used as natural dyes in cosmetic preparation were chosen because it is a cosmetic that is quite popular and most comfortable to use. The purpose of this research is to find out whether dragon fruit can be blush on, not irritated and to find out the best formulations. The methode of this research was done by making dragon fruit extract by maceration for 24 hours using etanol. The extract formulation used is 15%, 25%, and 40%. Ingridienst for making blush on include kaolin, parrafin liquid, zink oxyd, and talcum. Evaluation of blus on preparations include homogenty, pH, dispersion, irritation, polish and hedonic. The results of research 3 blush on formulation, the preparation met the homogenity test with no vissible coarse grains and particlesevently mixed. The pH of the preparation producted is still in the normal pH range of spearat evenly and easily attached to the skin, with each application three time polishing. Based on the favorite test after processing statistical data, formulation the most preferred panelish is blush on formulation 3. Key words: Dragon fruit, blush on, antosianin.